HCMV-encoded IE2 induces anxiety-depression and cognitive impairment in UL122 genetically-modified mice - Mu, Haiyu (Int J Clin Exp Pathol, 2019)
Although there is a high risk of mood disorders and cognitive impairment in congenital human cytomegalovirus (HCMV) infections, the molecular pathogenetic mechanisms of HCMV have not yet been fully determined. In this study, we show that immediate-early 2 (IE2) protein modulates affective and cognitive behaviors. We used a UL122 genetically-modified mice model that can continuously express IE2 protein. We used a series of animal behavior tests to determine the relationship between HCMV-encoded IE2 and psychiatric disorders. In open-field, elevated plus-maze test and tail suspension tests, we found that UL122 genetically-modified mice displayed more anxiety-depression behavior than did wild-type (WT) mice. The Morris water maze test and novel object recognition test showed that spatial learning and memory were lower in UL122 genetically-modified mice model than in WT mice. Level of fibroblast growth factor 2 (FGF2) protein in the hippocampus cornu ammonia areas (CA1, CA3) and dentate gyrus (DG) of the experimental group was significantly lower, consistent with immunohistochemical staining and western blot for neuron-specific nuclear protein (NeuN) and glial fibrillary acidic protein (GFAP). Levels of SYP and PSD-95 proteins were lower in the hippocampus UL122 genetically-modified mice. These data suggest the importance of HCMV-encoded IE2 for studying anxiety and depression behaviors and for the spatial learning and memory. This would help to further explain the molecular pathological mechanism of psychiatric disorders caused by HCMV infection.